Seven-Level PUC Inverter for Photovoltaic Systems with Buck-Boost Converter and P&O MPPT using Theta-Based Modulation (TMIM) - Al-Hajj, Baligh Belal Yahya Mohammed; Rini Nur Hasanah; Abraham Lomi (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2025)
This paper shows the design and simulation of a photovoltaic (PV) power conversion system based on a Seven-Level Packed U-Cell (PUC) inverter interfaced with a Theta-Based Modulation method and a Perturb and Observe (P&O) Maximum Power Point Tracking (MPPT) algorithm. The designed architecture focuses on overcoming significant challenges in PV systems, namely intermittent solar radiance, unstable voltage, and distortion of harmonics. Optimized by theta-based modulation for minimizing switching loss and overall harmonic distortion (THD), the PUC inverter topology stands out for its minimum number of components and superior output quality. A buck-boost converter controlled by the P&O MPPT algorithm is used for obtaining a maximum amount of energy from the PV array. Simulation on MATLAB/Simulink shows substantial performance improvements in terms of voltage stability, power quality, and energy efficiency under changing environmental conditions. The system integrated with the designed architecture proves a cost-effective and reliable method for improving the performance of PV systems and facilitating grid interface.